2004
DOI: 10.1159/000077676
|View full text |Cite
|
Sign up to set email alerts
|

11- to 15-Year-Old Children of Women Who Danced during Their Pregnancy

Abstract: Aim: To determine whether high levels of maternal physical activity (dancing during pregnancy), influenced the offspring. Materials and Methods: Sixty-four women (32 of whom had continued to dance for at least 2 months after the beginning of pregnancy) filled in a questionnaire to assess the health and behavior of their offspring, now 11–15 years of age. Results: More children born from women who had continued to dance during pregnancy needed to be rocked to sleep during their first year (p < 0.05). More child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…9,16,17 Additionally, passive swinging associated with dancing during pregnancy could potentially increase the heart rate of the fetus as well as fetal movement. 33 Because there have been controversial findings regarding the effect of exercise on fetal cardiac function during pregnancy, 34 the potential for fetal stress during the implementation of dancing during labor should be acknowledged. 34 Interestingly, along with potential unknown physical implications, there is a potential role in the development of the fetus's future personality and talents.…”
Section: Other Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,16,17 Additionally, passive swinging associated with dancing during pregnancy could potentially increase the heart rate of the fetus as well as fetal movement. 33 Because there have been controversial findings regarding the effect of exercise on fetal cardiac function during pregnancy, 34 the potential for fetal stress during the implementation of dancing during labor should be acknowledged. 34 Interestingly, along with potential unknown physical implications, there is a potential role in the development of the fetus's future personality and talents.…”
Section: Other Considerationsmentioning
confidence: 99%
“…34 Interestingly, along with potential unknown physical implications, there is a potential role in the development of the fetus's future personality and talents. 33 A survey study of professional dancers identified that mothers who danced throughout their pregnancy were more likely to have children who needed to be rocked to sleep during the first year of life and were more likely to play a musical instrument. 33…”
Section: Other Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, only two articles looked at the effects of dance during pregnancy. 3,4 To answer questions about what types of dance moves and levels of exertion are safe during pregnancy, the literature on exercise during pregnancy must be used. Exercise guidelines during pregnancy are provided by the American College of Sports Medicine (ACSM) 5 and the American College of Obstetricians and Gynecologists (ACOG).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a retrospective study, Bellieni and colleagues found that children born to women who danced during their pregnancy had a greater need to be rocked to sleep and a propensity for playing musical instruments. 4 When to Stop Dancing Except for vaginal and uterine symptoms, warning signs to stop exercise are the same for pregnant and nonpregnant women. Anyone who experiences any of the following symptoms should stop exercise immediately: dizziness or feeling faint, increased shortness of breath, chest pain, headache, muscle weakness, and calf pain or swelling.…”
Section: Fetal Outcomesmentioning
confidence: 99%